How to reduce wastes and save materials - Mohd. Ghazali, Mohd. Zulkifli; Kassim, Mohd. Azraai (1993)
Wastes either liquid or solid, are inevitable products of most of man's activities, whether urban or rural. Their type, amount and composition varies with the type of activity, be they domestic, industrial or agricultural in nature. Take the case of solid wastes. The waste that comes from agricultural, domestic, commercial, industrial as well as construction activities are composed of a wide variety of materials such as food wastes, construction wastes, papers, plastics, metals, garden wastes, factory offsets and process wastes, medical wastes and other discarded and residual items. Components that typically make up solid wastes in some cities in Malaysia are given in Table 1. The volume of wastes generated in major cities of Malaysia has also increased over the years due to increase in population, socioeconomic activities and physical development. Based on the statistical data during the 1980s, the quantity of municipal solid wastes of most of the urban centres have more than doubled in size. Johor Bahru which has the highest cost of living and is still rapidly expanding is no doubt producing an increasing volume of waste over the years due to the various development activities. The Johor Bahru Municipal Council collects more than 0.5 kg of waste per person per day amounting to about 400 tonnes per day. This figure is expected to increase to more than 0.8 kg/person/day by the year 1995 (Fan and Kheng, 1986). If improperly handled, these wastes will be a source of land, air, surface water and groundwater pollution. They must be collected, treated and/or disposed off properly. In order to achieve this, a good management system will have to be implemented and sufficient funds as well as skilled manpower be made available. With increasing costs of wastes handling, one of the attractive options of managing such wastes is to look into the possibility of wastes minimization and recovery.